Russian devils and diabolic conditionality in Nikolai Gogol's Evenings on a farm near Dikanka - Putney, Christopher (Lang, 1999)
In addition to examining the aesthetic representation of evil in Nikolai Gogol's Evenings on a Farm near Dikanka, this book explores the traditions of speculation into the devil found in Orthodox theology, medieval Russian literature, and East Slavic folklore. The author considers the evolution of Gogol's demonic idiom, as well as the numerous ways in which the shape of Gogol's devil develops according to theological, literary, and folkloric models of evil Offering a fresh and apt context for reading Gogol's Dikanka tales, this study also provides the first English-language overview of the devil in medieval Russian literature
Keywords: Gogolʹ; Nikolaĭ Vasilʹevich <1809-1852>; Gogolʹ; Nikolaj Vasilʹevič; Vechera na khutore bliz Dikanʹki; Večera na chutore bliz Dikanʹki; Avonden op een dorp bij Dikanka (Gogol); Duivel; Devil in literature; Russian literature; Teufel; Prosa